Numerical Simulation Study on Flow and Fracture of Granular Materials. (15th August 2019) - Liu, Mingqing; Liu, Jun; Liu, Guangkun; Shan, Peng; Xiao, Zhimin; Zhao, Futian
Abstract : Flow and fracture of granular materials under external loads is a complex mechanical process, and the research on its law is still in the exploratory stage. In this paper, the flow and fracture law of granular materials is taken as the research object, and numerical algorithm compilation and program development are combined to study. Taking full advantage of the existing algorithms and developing new ones based on the existing DEM theory, a numerical simulation program for the flow and fracture of granular materials is developed. The flow and fracture process of concrete spherical granular system with diameter of 4 cm under loading rate of 70 mm/min and end of loading of 50 kN is taken as an example to verify the simulation program. At the same time, the loading experiment of the concrete spherical particle system under the same simulation conditions was also carried out. The simulation results are compared with the experimental results in three aspects: the generation location of the particle system, the relationship between the whole load and displacement, and the degree of particle breakage. The results show that the numerical simulation is in good agreement with the experimental results, which verifies the reliability of the numerical algorithm and the simulation program, and can provide support for the study of the flow and fracture process of granular materials.